A Framework For Quality Management In Healthcare: From Hospital And Patient’s Perspective - Maryam, Waffa (2021)
A Master of Science thesis in Engineering Systems Management by Waffa Maryam entitled, “A Framework For Quality Management In Healthcare: From Hospital And Patient’s Perspective”, submitted in May 2021. Thesis advisor is Dr. Hussam Alshraideh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).